A sensitive isothermal fluorescence biosensor for microRNA detection coupling primer exchange reaction with catalytic hairpin assembly. Issue 5 (25th August 2022) - Liu, Jiatong; Shen, Minzhe; Talap, Jadera; Shen, Xudan; Song, Zihan; Hu, Haihong; Zeng, Su; Cai, Sheng
Abstract : A novel biosensor for sensitive detection of miRNAs was established based on coupling the primer exchange reaction (PER) with catalytic hairpin assembly (CHA). Abstract : The miRNA, which has been proven to regulate the expression of many cancer-related genes, is expected to become a new type of biomarker for cancer diagnosis and prognosis research. Herein, a novel biosensor for sensitive detection of miRNAs was established based on coupling the primer exchange reaction (PER) with catalytic hairpin assembly (CHA). A self-gated hairpin was designed as the template hairpin of the PER. Benefiting from the cascade PER and CHA, the proposed fluorescence biosensor showed high sensitivity and excellent selectivity for the miR-200a detection. Additionally, the biosensor was successfully applied for the detection of miR-200a from a diluted human serum sample. To sum up, the proposed fluorescence biosensor we established could be used as a highly sensitive platform. By replacing the specific sequences in the self-gated hairpin, the biosensor was promising to be used for simultaneous detection of various miRNA biomarkers in bioanalysis.